2021
DOI: 10.25135/acg.oc.97.2012.1895
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the in-silico approach for assessing the potential of natural compounds as a SARS-CoV-2 main protease inhibitors

Abstract: The SARS-CoV-2 virus emerged as a major cause of the COVID-19 pandemic in December 2019. Many attempts have been made to block the viral infection by targeting various processes like its entry, uncoating, replication, activating T cells response, and rising antibody titer. Also, many drugs are repurposed like remdesivir, dexamethasone, tocilizumab, hydroxychloroquine based on their established therapeutic efficacy against other viruses in the past. Natural products (NP) consist of a promising candidate and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Three plant compounds in Melissa officinalis extract, including luteolin-7-glucoside-3′-glucuronide, Metric acid-A and Quadranoside-III are known to be able to bind to these 2 proteins and deactivate them, thus showing antiviral activity. 32 , 34 , 120 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three plant compounds in Melissa officinalis extract, including luteolin-7-glucoside-3′-glucuronide, Metric acid-A and Quadranoside-III are known to be able to bind to these 2 proteins and deactivate them, thus showing antiviral activity. 32 , 34 , 120 …”
Section: Discussionmentioning
confidence: 99%
“… 32 Research has shown that 3 phytoconstituents from Melissa officinalis , including, Luteolin-7-glucoside- 3′-glucuronide, Metric acid-A, and Quadranoside-III have revealed better fusion affinity and solidity with the targets of SARS-CoV-2 main protease and spike protein. 33 , 34 …”
Section: Ribonucleic Acid (Rna) Virusesmentioning
confidence: 99%
“…In silico methods have been used in molecular biology for various analysis such as studying different receptors and ligands. By emerging of a global epidemic, many researchers sought to make it effective prevention and treatment strategies against COVID-19 using in silico , in vitro, and in vivo studies [ 25 ]. Regarding this pandemics, in silico methods have been used in different studies for analyzing the molecular structures of SARS-CoV-2 and even introducing potential therapeutic agents [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%